Study on Dynamic Evolution Law of Blasting Cracks in Elliptical Bipolar Linear Shaped Charge Blasting - Bo Wu; Shixiang Xu; Guowang Meng; Junhua Cai; Han Wei; Hualong Li; Jinglong Zhang (Shock and Vibration)
Based on LS-DYNA numerical simulation analysis and comparison with laboratory tests, the blasting crack development dynamic evolution mechanism of elliptical bipolar linear shaped charge is analyzed. The development law of rock crack and optimal radial decoupling coefficient under different blast hole diameters were studied. The results revealed that the blasting with elliptical bipolar linear shaped charge had a remarkable effect on the directional crack formation, and the maximum effective stress of rock close to the position of shaped charge in the direction of concentrating energy is about 2.3 times of that in the direction of nonconcentrated energy. Moreover, the directional crack could be formed by blasting with elliptical bipolar linear shaped charge with different hole diameters, whilst the length of the main crack was related to the radial decoupling coefficient. Particularly, the main crack reached the longest when the radial decoupling coefficient was 3.36.